2009
DOI: 10.1161/strokeaha.108.540500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Peripheral Nerve Stimulation and Brain Polarization on Performance of a Motor Sequence Task After Chronic Stroke

Abstract: Background and Purpose-Recent work demonstrated that application of peripheral nerve and cortical stimulation independently can induce modest improvements in motor performance in patients with stroke. The purpose of this study was to test the hypothesis that combining peripheral nerve stimulation (PNS) to the paretic hand with anodal direct current stimulation (tDCS) to the ipsilesional primary motor cortex (M1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
164
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 43 publications
7
164
2
5
Order By: Relevance
“…Previous unihemispheric brain stimulation studies revealed transient beneficial effects after modulation of either ipsilesional 7,10,11,14 or contralesional motor cortex excitability. 9,12 The novel bihemispheric stimulation design used in the present study allowed us to test the efficacy of simultaneously affecting both components of the hypothesized imbalance of interhemispheric interactions after stroke.…”
Section: Seconds[log] (Post 2)mentioning
confidence: 97%
See 3 more Smart Citations
“…Previous unihemispheric brain stimulation studies revealed transient beneficial effects after modulation of either ipsilesional 7,10,11,14 or contralesional motor cortex excitability. 9,12 The novel bihemispheric stimulation design used in the present study allowed us to test the efficacy of simultaneously affecting both components of the hypothesized imbalance of interhemispheric interactions after stroke.…”
Section: Seconds[log] (Post 2)mentioning
confidence: 97%
“…Furthermore, the multisession design of the present study cannot be easily related to previous single session experiments of chronic stroke patients. 11,12,14 To adequately compare the efficacy of different tDCS montages in combination with peripheral sensorimotor stimulation and to assess differences in short-term and longer-term functional improvements, larger patient samples are needed. Furthermore, although we chose to combine tDCS with PT/OT, which is commonly applied in routine poststroke rehabilitation, more standardized peripheral stimulation programs such as constraintinduced movement therapy may be an alternative in future studies.…”
Section: Figure 3 Contrast Of Affected Limb Movements Postinterventiomentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the association of tDCS with peripheral nerve electrical stimulation, aerobic exercise or conventional physiotherapy improves pain and motor function in a more pronounced way than these interventions per se [8][9][10][11][12][13] . These results have been interpreted on the basis of the meta plasticity phenomenon 14 .…”
mentioning
confidence: 99%